Techniques for Studying Actual Usage of Personal Communication Prototypes - Tang, John; Junuzovic, Sasa; Inkpen, Kori; Venolia, Gina (Studying and Designing Technology for Domestic Life, 2015)
Developing new prototypes for supporting personal communication raises many challenges in studying them in actual usage. Personal communication tools are often only used with specific people (i.e., close friends and relatives), and often rely on the context of the home or other locations of personal interest. Thus, these prototypes are not readily studied in the lab with strangers. We report on three methods we have employed to study how social communication prototypes are used out in the wild. One method was to embed ourselves along with a prototype into an intact social group. Another method was to observe the use of a prototype in shared activities happening outside the home whenever and wherever the activities occurred. The third method was to passively capture shared experiences that people do on their own time and analyze them at a later point. We reflect on our experiences and the opportunities and challenges that we have identified in this research area.